“The facilitator is not a bystander”: exploring the perspectives of interdisciplinary experts on trauma research - Hira, Sarita; Sheppard-Perkins, Madeleine; Darroch, Francine E. (Frontiers in Psychology, 2023)
Objective This study investigates the concepts, knowledge, and guiding principles that inform the practice of professionals researching trauma or working directly with individuals who have lived and living experiences of trauma. These aspects are explored with the aim of identifying current practices and potential gaps which may contribute to more trauma-informed biomarker-based research approaches. Method The perspectives of experts were explored through semi-structured interviews with seven participants; these individuals represented trauma research, clinical practice, and trauma-informed physical activity domains. Results A thematic analysis of the collected data revealed three focal areas highlighted by participants from all disciplines: “If I want to know trauma in the body of a person I need to know the person’s language” which related to experiences of discussing trauma with clients; “What all people need is a safe place” relayed the importance of safety for participants working with the trauma expert; and “the facilitator is not a bystander” framing trauma-related work as a collaborative process between participants and their care providers. Conclusion Evidence of formal implementation of trauma-informed practices within research settings is lacking. This gap is identified within background literature, while the importance of implementing these practices is emphasized by the participants of this study. This presents an opportunity to apply the insights of the interviewed experts toward advancing trauma research methodologies. Adapting biomarker-based research methodologies to fit a trauma- and violence-informed model may have benefits for the quality of participant experiences, research data, and knowledge of effective interventions.